PERSEPSI WISATAWAN TERHADAP WISATA PANTAI DI KELURAHAN PECATU KABUPATEN BADUNG DALAM PERENCANAAN PAKET WISATA - Ida Bagus Made Widyasmara; I Made Kusuma Negara; I Wayan Suardana (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2013)
This field study aims to determine the perception of tourists to the beaches in Pecatu Village Badung Regency. The results can be used to plan the tour packages according to tourist perceptions of the tourist beaches in Bali. Analysis techniques used in this research is the analysis of quantitative and qualitative. Analysis techniques in this study using quantitative descriptive. Discussion of the results obtained in this study that the variables are extremely assessment given by tourists on beaches in Pecatu Village Badung Regency can already make tourists satisfied, must be maintained both management and development of the beaches, because there are still some variables that need to be addressed or equipped to make the tourists who come will still feel satisfied the beaches in Pecatu Village Badung Regency. The results of this study on the perception of tourists to the beaches in Pecatu Village Badung Regency can be suggested to the travel industry as feedback in planning the manufacture of package tours. In addition to government and related managers, the results of this study can be a thought or input for the management and development of coastal tourism in accordance with the perception of tourists.